A new design of drag-free and attitude control based on non-contact satellite. (May 2019) - Liao, He; Xu, Yufei; Zhu, Zhu; Deng, Yifan; Zhao, Yanbin
Abstract: A novel non-contact satellite for drag-free and attitude control is proposed in this paper. The non-contact satellite is separated into a payload module and a service module by non-contact Lorentz actuators. Instead of thrusters, the non-contact Lorentz actuators are used to exerted precise forces and torques, enabling drag-free and attitude control of the payload module, while the service module is designed to track the payload module to avoid collision. On the basis of this new design, the dynamics of drag-free and attitude control can be precisely modeled. Accordingly, a hierarchical control algorithm, consisting of an EKF-based estimation and rejection of environmental acceleration of payload module, attitude control of payload module, minimum norm allocation of non-contact Lorentz actuators, as well as collaborative control of service module, is systematically designed. A numerical simulation is then conducted to demonstrate the validity and effectiveness of the proposed design. Graphical abstract: Highlights: Drag-free and attitude control based on non-contact satellite is proposed. This technique relies on non-contact Lorentz actuators which provide precise forces. An hierarchical control law consists of EKF-based estimation is designed. Numeric simulation demonstrates the validity and effectiveness of the design.